PARADIGM OF DIGITAL TRANSFORMATION OF ENTERPRISE BUSINESS PROCESSES - FERNANDEZ, Rea Christian Elias (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The article is devoted to the actual problem of substantiation of scientific and methodological provisions and development of practical recommendations on the paradigm of digital transformation of business processes of enterprises. It is determined that for successful operation in the market, enterprises must develop a business model to create value for customers and make a profit by the company. Five main areas covered by digital transformation are revealed: business model transformation, automation and optimization of business processes, innovation in digital products and services, empowerment and employee engagement, and customer interaction. The definition of "digital transformation" is given as the integration of digital technologies into all business areas, which radically changes the principles of enterprise operation and providing value to customers. The advantages that enterprises that make the transition to the digital transformation paradigm receive are revealed: a better understanding of market trends; expanding markets and sales channels; ensuring compliance with customer expectations and meeting their needs; increasing customer loyalty; expanding opportunities to reduce costs and increase profitability. The stages of forming a digital transformation strategy are substantiated, which consist in the following: defining the mission and strategic vision; auditing the existing business strategy; reviewing business processes to add value to the product using digital technologies; defining your own priority projects; developing a system of necessary competencies; outsourcing of functions to partners or external organizations; identification of key indicators of the organization's development and measures to implement the strategy; optimization of the management process and formation of Digital Culture; selection of the most effective digital technology. Companies that have successfully applied digital technologies to transform their business in various fields of activity are represented: Walmart in retail, Mayo Clinic – medical services, investment bank Goldman Sach, travel and hotel company Airbnb, car manufacturer Toyota.
Keywords: paradigm; strategies; digital transformation; digital technologies; digitalization; business processes